The Association between NLR and TGF-β with Acute Ischemic Stroke Severity with and without Thrombolysis - Lesti Marliana; Syarif Indra; Dedi Sutia; Yuliarni Syafrita; Restu Susanti; Fanny Adhy Putri (Jurnal Ners, 2025)
Acute ischemic stroke is a leading cause of mortality worldwide. Thrombolysis is the main treatment in the acute phase; however, clinical outcomes remain variable. Inflammatory markers such as the NLR and TGF-β1 may reflect inflammatory activity and tissue repair, yet their relationship with stroke severity is not fully established. This study aimed to evaluate the association of NLR and TGF-β1 with acute ischemic stroke severity in patients with and without thrombolysis. A cross-sectional study was conducted in the neurology ward of Dr. M. Djamil General Hospital, Padang. Patients with acute ischemic stroke, either treated with thrombolysis or not, were included. NLR and TGF-β1 were measured at 24 hours after onset, while stroke severity was assessed using the NIHSS at 24 hours. A total of 25 thrombolyzed and 25 non-thrombolyzed patients were enrolled. The results showed no significant association between NLR and stroke severity in either the thrombolysis (p=0.123) or non-thrombolysis group (p=0.257). In contrast, TGF-β1 was significantly associated with stroke severity in both groups (p<0.001 and p=0.002, respectively). In conclusion, TGF-β1 correlates with acute ischemic stroke severity regardless of thrombolysis, while NLR shows no significant association.